Strategy Development Augmented Reality: Integrasi Concept Stimuli Organism Respon, Open Innovation, and Organizational Performance - Mochamad Aldi Alisodikin; Endang Chumaidiyah; Iphov Kumala Sriwana (Eduvest - Journal of Universal Studies, 2025)
The development of digital technology has encouraged the adoption of Augmented Reality (AR) as a strategic innovation in various industries, but its application in Indonesia remains limited due to low awareness and a lack of an integrated innovation strategy. This research aims to develop a strategy to strengthen AR technology through the integration of the Stimuli-Organism-Response (SOR) model, the concept of Open Innovation (OI), and Organizational Performance (OP), with a case study on PT. X in the city of Bandung. A mixed methods approach was applied, combining qualitative and quantitative analysis using the Fuzzy Analytical Hierarchy Process (F-AHP) method to determine the priority of the strategy, as well as Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between variables. The results showed that stimuli in the form of interactivity, augmentation, and AR aesthetics had a significant influence on internal organizational factors (organisms) and subsequently affected user behavioral responses, including reuse intentions. Meanwhile, open innovation plays an important role in strengthening organizational competitiveness through external collaboration, with inbound innovation being the most dominant factor. The research also resulted in three main strategies: improving interactive features and user experience, developing high-quality visual content, and strengthening collaborative networks through open innovation. The integration of SOR, OI, and OP models has proven effective in shaping a holistic, data-driven AR development strategy. The conclusion states that this approach can increase the adoption of digital technology and make a real contribution to organizational performance and digital economic growth in Indonesia.